Predição do consumo de oxigênio na doença pulmonar obstrutiva crônica e o impacto da síndrome overlap na capacidade máxima de exercício - Carvalho Junior, Luiz Carlos Soares de (Universidade Federal de São Carlos, 2018)
The chronic obstructive pulmonary disease (COPD), a very prevalent in clinical practice, presents complex pathophysiology because in addition to pulmonary alterations, it affects multiple organs and systems. In this way, understanding the impact of the disease on the health of the individual is a challenging task for clinical management. cardiopulmonary exercise test (CPET) is highlighted in this scenario, since it is the gold standard method to evaluate cardiorespiratory fitness (CRF), expressed by oxygen uptake at the peak of exercise (V̇O2peak), an important prognostic marker in COPD. In addition, CPET provides cardiovascular, pulmonary, and muscular responses to maximal dynamic exercise for better understanding the magnitude of the damages caused by COPD. Such alterations may be even more evident when besides the COPD there is the obstructive sleep apnea syndrome (OSAS) coexisting in the individual, characterizing the so-called overlap syndrome. OSAS also presents high prevalence and association with exercise intolerance as well as COPD. However, despite the clinical evidence of its relevance, the CPET is still underutilized, possibly due to the high costs involved and the complexity to interpret a large number of variables obtained from the evaluation report. In this sense, two studies are presented in this thesis and they were developed for the following purposes: 1) to understand the correlation of CRF with variables evaluated by low-cost and routine clinical methods and, from these, to estimate the V̇O2peak in individuals with COPD; 2) to evaluate the impact of the overlap syndrome on the cardiovascular, pulmonary, and muscular systems during the maximal dynamic exercise of COPD individuals. In the first study, titled “CAT and FEV1: Can they predict maximal oxygen uptake in COPD?”, twenty-seven individuals with COPD performed a clinical evaluation (anamnesis, anthropometric data collection, COPD Assessment Test - CAT, and spirometry) and the CPET. In the first study, titled “CAT and FEV1: Can they predict maximal oxygen uptake in COPD?”, Twenty-seven assistants with COPD underwent COPD-CAT evaluation, spirometry) and in the second performed CPET. The results showed that V̇O2peak correlated directly with forced expiratory volume in the first second (FEV1) and inversely with the CAT questionnaire score. Moreover, these easy and wide used variables in clinical practice can be applied - individually or associated - in mathematical models to estimate the V̇O2peak. In the second study, titled "Overlap Syndrome: OSAS coexistence further compromises cardiorespiratory fitness in COPD", thirty-one individuals with COPD performed clinical and spirometry evaluations. Subsequently, the volunteers received a home visit for sleep evaluation and, according to data obtained, they were divided into COPD group or overlap syndrome group (COPD in coexistence with OSAS). In another visit to the laboratory, the volunteers performed the CPET. In order to better understand the effect of overlap syndrome, we subdivided the individuals into four groups, according to the severity of COPD and the coexistence of OSAS (COPD I / II, overlap I / II, COPD III / IV, overlap III / IV). We conclude that the coexistence of OSAS in the individual with COPD elicited increased hemodynamic and ventilatory responses to maximal aerobic exercise in comparison to COPD isolated. In addition, individuals with severe and very severe COPD present greater losses in CRF and circulatory power in the OSAS coexistence than those ones with lower severity of the disease and no overlap syndrome.
Prediction of oxygen uptake in chronic obstructive pulmonary disease and the impact of overlap syndrome in the exercise capacity
Keywords: Doença Pulmonar Obstrutiva Crônica; Síndrome da Apneia Obstrutiva do Sono; Sintomas; Espirometria; Consumo de Oxigênio; Aptidão cardiorrespiratória; Chronic Obstructive Pulmonary Disease; Obstructive Sleep Apnea Syndrome; Symptoms; Spirometry; Oxygen uptake; Cardiorespiratory fitness; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL